The Effect of Health Education on Knowledge of The Prevention of Diabetes Mellitus - Dewi Wijayanti (Babali Health, 2022)
Introduction: Diabetes mellitus (DM) is a lifelong disease that cannot be cured permanently, which according to WHO estimates the number of people with diabetes will be the main cause of 7 deaths in 2030. One way to reduce the incidence of diabetes mellitus is to provide education about diabetes mellitus in the community so that early prevention of DM can be done. This study aims to determine the effect of health education on knowledge of diabetes mellitus prevention in the community of RT.03 Mambirdan Tarakan, North Kalimantan. Methods: The design of this study used an experimental one group pre post test design, with a sample size of 31 respondents, data collection using a diabetes mellitus knowledge questionnaires. The test carried out was a paired t test. Results: Knowledge increased by 58.06% with p= 0.001 < 0.05. There is a significant effect of effectiveness on the level of anxiety in elderly patients suffering from diabetes mellitus in the Al-Marhamah Tarakan nursing home, North Kalimantan. Conclusion: Health education has an effect on increasing knowledge of diabetes mellitus prevention in the community of RT.03 Mambirdan Trakan, North Kalimantan.